Population Dynamics Reveal a Core Community of the Common Bottlenose Dolphin (Tursiops truncatus) in Open Waters of the South-Western Gulf of Mexico - Bolaños-Jiménez, Jaime; Morteo, Eduardo; Delfín-Alfonso, Christian A.; Fruet, Pedro F.; Secchi, Eduardo R.; Bello-Pineda, Javier (Frontiers in Marine Science, 2021)
The presence of transient and temporary individuals in capture-mark-recapture studies may violate the assumption on equal catchability, and thus yield biased estimates. We investigated the effects of residency patterns on population parameters of bottlenose dolphins inhabiting the coastal waters off the Alvarado Lagoon System (ALS), Veracruz, Mexico. We hypothesized that this population is open but there exists a “core community” that behaves as a closed population. Between 2006 and 2010, we conducted 75 photo-identification surveys and recorded 263 dolphin group encounters, in which 231 dolphins were identified. Individuals present during only one season, classified as transients (n = 85), were excluded from the study, and a standardized residency index (IH4) was computed for each dolphin that remained in the sample (n = 146). We used the K-means clustering method to split the sample into groups based on individual (seasonal, annual) IH4 values. These clusters were named as regular residents (RR, n = 55), occasional residents (OR, n = 45), and occasional visitors (OV, n = 46). The cumulative frequency of newly identified individuals displayed an asymptotic trend for the whole sample and all clusters, indicating that most of the individuals present in the study area during the study period were identified. The assumption of demographic closure was tested to define the core community, and was rejected for the whole sample and the OV cluster (p < 0.001 in both cases), indicating that the population is open. The closure assumption was not rejected for RR and OR clusters (χ2 = 6.88, DF = 13, p = 0.91, and χ2 = 17.8, DF = 16, p = 0.33, respectively), indicating that these clusters were demographically closed over the 5-year period. Thus, we defined this aggregation of individuals as the “core community”. The closed population model Mth indicated that the total abundance of this core community was 123 individuals (95% CI: 114–133). Our results provide quantitative evidence of the existence of a core community in open waters of the Gulf of Mexico, and points toward residency pattern as a main driver of population dynamics. These results highlight the importance of considering residency patterns when dealing with heterogeneity in the sample of a highly mobile species.